Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/5491676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin D Status in Rheumatoid Arthritis and Its Association with Disease Activity across 15 Countries: “The COMORA Study”

Abstract: The aims of this study are to evaluate vitamin D status in 1413 RA patients of COMORA study from 15 countries and to analyze relationship between patients' RA characteristics and low levels of vitamin D. All demographic, clinical, and biological data and RA comorbidities were completed. The results showed that the average of vitamin D serum dosage was 27.3 ng/mL ± 15.1 [0.1–151]. Status of vitamin D was insufficient in 54.6% and deficient in 8.5% of patients. 43% of RA patients were supplemented with vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Also, a report including data of 15 different countries confirms variation of serum D vitamin levels [31]. This difference is explained due to the differences in people such as ethnic variation, climate, sun exposure, dressing style or latitude [7,31]. Since this study was performed in a rural area of Turkey, ethnic variations were not noted.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Also, a report including data of 15 different countries confirms variation of serum D vitamin levels [31]. This difference is explained due to the differences in people such as ethnic variation, climate, sun exposure, dressing style or latitude [7,31]. Since this study was performed in a rural area of Turkey, ethnic variations were not noted.…”
Section: Discussionmentioning
confidence: 67%
“…It was published that more vitamin D intake reduces the prevalence of RA in Northern Europe compared with Southern Europe [7]. Also, a report including data of 15 different countries confirms variation of serum D vitamin levels [31]. This difference is explained due to the differences in people such as ethnic variation, climate, sun exposure, dressing style or latitude [7,31].…”
Section: Discussionmentioning
confidence: 96%
“…Many literature sources have reported a negative association between vitamin D level and age (Mithal et al, 2009;Anonymous, 2014;Hajjaj-Hassouni et al, 2017). This trend might be explained by vitamin D replacement therapy given often to infants and toddlers, which is discontinued as the child grows.…”
Section: Discussionmentioning
confidence: 99%
“…In RA patients, the efficacy of vitamin D intervention is controversial. Indeed, a large number of studies have confirmed that vitamin D deficiency exists in RA patients in different countries and low levels of vitamin D are associated with increased disease activity, glucocorticoid dosage and RA complications [16]. Another study documented an inverse correlation between the severity of depression and anxiety in RA patients and the level of serum vitamin D3 [17].…”
Section: Sift Deskmentioning
confidence: 99%